GAMBARAN KELENGKAPAN IMUNISASI DASAR LENGKAP (IDL) DI WILAYAH KERJA PUSKESMAS PENEBEL 1 TAHUN 2022 - Apriani, Desak Gede Yenny Gede Yenny (Jurnal Ayurveda Medistra, 2023)
Background : Immunization is the most effective and efficient public health effort in preventing several dangerous diseases. Routine immunization coverage in Indonesia is still in the unsatisfactory category, where Pentavalent and MR coverage does not reach 90% of the target even though the basic immunization program is provided free of charge by the government at Puskesmas and Posyandu. Objective : The purpose of this study was identify the description of the achievement of complete basic immunization at Puskesmas Penebel I.. Method : This study uses a quantitative descriptive design. The population in this study were mothers who had babies aged 9-12 months at Puskesmas Penebel I as many as 74 people with a total sampling technique. Data collection was carried out by observing the baby's health card (KMS). Then the data is tabulated to get the frequency distribution of the characteristics of the respondents and the achievement of complete basic immunization. Result : The results of this study were 71.6% of respondents aged 20-26 years, 52.7% of mothers who graduated from high school, 51.4% of them worked as entrepreneurs, most of the distance between the respondents' homes and health services was 1km, most of the mothers most of them received support from their families, and most of the complete basic immunization results were obtained in the complete category of 85.1%. Conclusion : The achievement of complete basic immunization at Puskesmas Penebel I was 85.1%.